Application of visual placement of a nasojejunal indwelling feeding tube in intensive care unit patients receiving mechanical ventilation - Chen, Yuequn; Tian, Xin; Liu, Cheng; Zhang, Liqin; Xv, Yueyuan; Xv, Shuang (Frontiers in Medicine, 2022)
Background Compared with nasogastric nutrition, nasojejunal nutrition may prevent some complications of critically ill patients by maintaining better nutritional status, and blind placement of nasojejunal dwelling feeding tubes is widely used. However, the visual placement seems to be safer and more effective than the blind placement, and is still seldom reported. Objective We tried to develop visual placement of a nasojejunal feeding tube in intensive care unit patients. Method A total of 122 patients receiving mechanical ventilation were admitted to the Department of Critical Care Medicine of the Fifth Affiliated Hospital of Wenzhou Medical University and received the placement of nasojejunal feeding tubes. These patients were randomly and evenly assigned into two groups, one group receiving visual placement of nasojejunal dwelling feeding tubes and another group receiving blind placement. Actual tube placement was confirmed by X-ray. The primary outcome included the success rates of first placement of feeding tubes. The secondary outcome included the time of tube placement, complications, the total cost, heart rates and respiratory rates. Result The primary outcome showed that the success rates of first placement were 96.70% (59 cases/61 cases) in the visual placement group, and two cases failed due to pyloric stenosis and gastroparesis. The success rates were 83.6% (51 cases/61 cases) in the blind placement group and 10 cases failed due to either wrong placement or retrograde tube migration. The success rates in the visual placement group were higher than that in the blind placement group (P=0.015). The secondary outcome showed that the time of tube placement in the visual placement group was shorter than that in the blind placement group (P<0.0001). The cost of tube placement in the visual placement group was higher than that in the blind placement group (P<0.0001). The statistical differences in complications, heart and respiratory rates were insignificant between the two groups (P>0.05). Conclusions Compared with the blind placement, the visual placement shortened the time of nasojejunal tube placement and increased success rates of first placement. The visual placement was more efficient, easy to operate, safe, and has potential clinical applications.